A Subacute Toxicity Test of Rhizophora apiculata Stem Bark Ethanol Extract on the Number, Motility, and Morphology of Male Rattus Norvegicus Spermatozoa - Syazili Mustofa; Rheza Paleva (Sriwijaya Journal of Medicine, 2023)
Indonesia has the largest mangrove ecosystem in the world. Rhizophora apiculata is a mangrove often used as traditional medicine by Indonesians. It has previously been researched that the ethanol extract of Rhizophora apiculata stem bark has benefits as a source of natural antioxidants. However, there has yet to be much research on the toxicity of this extract. Therefore, researchers want to know the subacute toxic dose of Rhizophora apiculata bark extract on fertility parameters. The type of research is experimental research with a completely randomized research design. The sample consisted of 30 male rats, which were divided into 5 groups, namely the control group, which received no treatment, and the P1-P4 treatment group, which was given Rhizophora apiculata bark extract every day with 4 dose levels starting from 114 mg/kg BW to a dose of 912 mg/kg BW for 28 days. On day 30, the rats were euthanized, and the fertility parameters of the rat spermatozoa were examined using a microscope. Kruskal-Wallis analysis and One-Way ANOVA showed p<0.05 for the spermatozoa's number, motility, and morphology. The toxic dose that can reduce the number of spermatozoa is found at 912 mg/kg BW; the toxic dose that reduces spermatozoa motility is 228 mg/kg BW; and the toxic dose that affects spermatozoa morphology is 456 mg/kg BW. This research concludes that the subacute toxic dose of the ethanol extract of Rhizophora apiculata stem bark against the spermatozoa of the male Rattus norvegicus Sprague Dawley strain in the subchronic toxicity test was 228 mg/kg BW.